Conditions and Problems of Instructional Management in Saxophone Practical Skills Course in Higher Education Institutions in Thailand - Kittikun Jungate,; Sayam Chuangprakhon,; Weerayut Seekhunlio,; Suthasinee Theerapan, (Journal of Educational Issues, 2024)
The objectives of this research were 1) to study the conditions and problems of instructional management in the Saxophone Practical Skills course in higher education institutions in Thailand, and 2) to propose guidelines for developing the instructional management in the Saxophone Practical Skills course in higher education institutions in Thailand. It is qualitative research. It applied the method of interviewing and observing instructors teaching the Saxophone Practical Skills course in higher education institutions in Thailand, a total of 9 people. The data was then analyzed, the content synthesized, and descriptive reports were written. The research results showed that 1) instructional management in the Saxophone Practical Skills course uses two teaching principles and methods: Classical Saxophone and Jazz Saxophone. Problems encountered in the instruction are the embouchure, air support, tone quality, articulation, performance techniques, understanding of musical performance, the condition of the learner's instruments, and the insufficient places of training for the learner, and 2) the guideline for developing the instructional management consists of to choose the suitable teaching method that the individual learners, encourage students to perform soloists or band members, and attend musical performances.